Automatic analysis of nonmetallic inclusions in steel using electron microscope with energy dispersive microprobe with - T. I. Sidorenko; V. I. Voznaya; Yu. S. Belash; E. V. Ermachenok (Литьë и металлургия, 2022)
Clean steel non-metallic inclusions have a significant effect on the physic and mechanical as well as technological properties of the metal and consequently on the quality of the final product. There are many methods for detecting and evaluating nonmetallic inclusions. Traditional methods for assessing the contamination of metal with microinclusions are metallographic methods, which are divided into methods for comparing the contamination of the section with inclusions with reference scales and counting methods. The classification of inclusions by traditional methods on a polished section is based on morphological features: shape, color, aspect ratio, etc. In addition to traditional optical microscopy, an electron microscope is used for studies that are more detailed. Equipping an electron microscope with an attachment for energy-dispersive microanalysis allows classifying nonmetallic inclusions by chemical classes. As a result of the implementation of a set of organizational and technical measures, BMZ, the management company of BMK Holding, installed and put into operation research equipment in December 2020 – a scanning electron microscope with an energy-dispersive microanalyzer (SEM with EMF). Thanks to the software module that the microanalyzer is equipped with, the possibility of automatic analysis of non-metallic inclusions is implemented. The software settings include the search for non-metallic inclusions and their classification according to widely used international standards. The flexible configuration of the software allows you to create models for separating inclusions into different user classes.